Jimmy Carter - Zelizer, Julian E (New York : Times Books, 2010)
An examination of Carter's presidency and his emergence as an important voice for international diplomacy and negotiation
Maverick politician -- New southern politics -- Outsider wins -- Year of promise -- Conservatives rising, democrats dividing -- Falling apart -- Last year -- Pariah diplomacy -- Epilogue
Includes bibliographical references (p. 151-163) and index
Keywords: Carter, Jimmy, -- 1924-; Presidents -- United States -- Biography; United States -- Politics and government -- 1977-1981; Southern States -- Politics and government -- 1951-